Identification of the Key Factors in Building Destination Brand Using Events: Lessons for Taiwan - Hsu, Ming-Hsiang (2010)
This dissertation considers the implication of special events in destinations and focuses on the effect of co-branding in relation to the image transfer between events and destinations. Researches regarding the effects of special events and the factors contributing to co-branding have been carried out through qualitative interviewing. The research design undertaken allows the study to gain an insight from potential tourists’ attitudes and perception of event related tourism. A number of critical factors which reinforce the relationship between events and destination brand are identified. It is concluded that media promotion and differentiation are of the top priorities when using events as a marketing approach. In addition, a marketing framework is proposed to fill in the research gap regarding the strategic use of events in destination branding process. The critical factors that help building destination brand image are highlighted to further apply in Taiwan’s event tourism development. This may be of interest to destination marketers, event organisers, especially in developing destinations which intend to differentiate themselves from the competitive market.